Digital-Enhanced Collaborative Learning: Integrating the STAD Model with Canva to Improve Interest and Social Studies Outcomes - Rode Putra; Ismira Ismira; Hafiz Hidayat (Journal of Education Research, 2026)
Effective social studies instruction at the elementary level requires both engaging cooperative learning structures and visually stimulating instructional media. This study aimed to analyze the effects of the Student Teams-Achievement Divisions (STAD) cooperative learning model integrated with the Canva application on students' learning interest and social studies learning outcomes. A quantitative quasi-experimental pretest-posttest control-group design was employed, with 43 fifth-grade students at SD Negeri 41/III Koto Beringin as research subjects, comprising 22 students in the experimental group and 21 in the control group. Data were gathered using a validated learning interest questionnaire and a learning achievement test, then analyzed using independent-samples t-tests, N-gain scores, and descriptive statistics. The results showed that students in the STAD-Canva treatment group demonstrated significantly higher learning interest and academic achievement compared to those receiving conventional instruction (t = 5.34, p < .05), with an N-gain index of 0.68 (moderate-high category) in the experimental group versus 0.41 (moderate category) in the control group. These findings indicate that combining STAD with Canva as a visual media tool constitutes an effective and replicable strategy for enhancing elementary social studies education, particularly in contexts where low-cost digital tools can be integrated within structured cooperative frameworks.